PROBLEMS IN TRANSLATION QUALITY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Translation plays a crucial role in cross-cultural communication by enabling the transfer of meaning between languages. However, achieving high translation quality remains a significant challenge due to linguistic, cultural, and contextual differences between the source and target languages. This article examines the main problems affecting translation quality, including lexical ambiguity, grammatical differences, cultural untranslatability, stylistic inconsistency, and the influence of machine translation. Special attention is given to the role of the translator’s competence and background knowledge. The study emphasizes that translation quality depends not only on linguistic accuracy but also on pragmatic equivalence and cultural awareness.